그린 바나나 분말을 이용한 컵케이크의 품질특성에 관한 연구 - 김미수(Mi-Soo Kim); 양지원(Ji-Won Yang); 이경희(Kyung-Hee Lee) (동아시아식생활학회지, 2019)
This study examined the product quality characteristics of cupcakes made using green banana powder, which despite being rich in resistant starch and mass producible, is not commonly used. Cupcakes were made by adding green banana powder in quantities of 20%, 40%, 60%, or 80% relative to the wheat flour content, and their physicochemical and sensory characteristics were evaluated. The specific gravity of the cupcakes showed an increasing trend with increasing green banana powder content (0.89∼0.92). The moisture content (25.4∼28.5%) and mass (52.5∼54.1 g) increased with increasing green banana powder content, while the pH (6.83∼6.29), specific volume (1.9∼1.5), baking loss (12.5∼9.8%), volume (103.3∼81.7 mL), and height (6.1∼4.2 cm) showed decreasing trends with increasing green banana powder content. In color analysis, the L values (73.4∼ 49.6) and b values (40.6∼22.6) decreased with increasing green banana powder content, while the a values (—0.8∼2.6) showed an increase. Among the texture characteristics, the hardness increased significantly with increasing green banana powder content, and the cohesiveness and resilience decreased significantly with decreasing green banana powder content. In the sensory evaluation, a preference test showed that green banana powder content in the range of 20∼40% produced the highest overall preference, as well as taste and texture preference, but not appearance preference. In the preference-difference test according to the characteristics, increasing green banana powder content was associated with decreased volume and stronger color inside of the cupcake. In addition, the taste was rated as less sweet and less cloying, and there was a strong smell of bananas. Overall, the use of 20∼40% green banana powder could result in cupcakes with high preference. KCI Citation Count: 1